The language attitude of Islamic boarding school students toward English - Dwijani Ratnadewi; Eka Utami; Sofi Yunianti (Intelektual Pustaka Media Utama, 2020)
Language attitude study has proven to reveal students’ success and failure in learning language. Attitude is not innate, but learned. Students learn to grow and improve their positive language attitudes towards foreign languages through certain programs at schools. The aim of this research is to investigate the language attitude of students in an Indonesian Islamic boarding school towards English as a foreign Language and to describe why they have the attitude. The respondents were 49 students of 2nd grade of senior high school classes from HAC (High-Achieving Class) and LAC (Low-Achieving Class). The design of this research was mixed method using explanatory sequential design. To obtain the data, the instrument used was a questionnaire consisting of cognitive, affective and conative components of language attitudes. Interview was carried out to acquire the reason the students had the attitudes. The finding was both HAC and LAC students’ language attitudes were mostly positive (91.83%) in cognitive, affective and conative language attitudes. Some (8.17%) had different language attitudes. They showed positive language attitudes, but acquired low scores and showed negative language attitudes, but acquired high scores. The interview revealed this phenomenon.